ANALISIS KEADAAN PEREKONOMIAN PRA OLIMPIADE DAN PASCA OLIMPIADE - Ferry Vincenttius Ferdinand; Timothy Sean Muliadiredja; Jonathan Christian (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. Being the host of the Olympics is an honor in itself. Because by hosting the Olympics it is hoped that it will have a good impact on the country's economy. Many countries in the world are competing to host the Olympics, and indeed the results of several countries do have an impact on the country's economy. With this data, it was also found that there were very significant changes in the economies of countries that hosted the Olympics, such as Bei Jing and Brazil. By using benchmarks based on GDP Growth, Unemployment and Foreign Direct Investment, it is expected to be able to answer the economic growth of each country that is hosting the Olympics.